KETIDAKADILAN GENDER PADA NOVEL YUNI KARYA ADE UBAIDIL DAN NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO - Maguna Eliastuti; Shania Zaki Rahmah; Fina Astari Sa’adah; Gita Setyaningrum; Susanti Eka Sari (Bajang Institute, 2023)
The purpose of this research is to compare cultural values ​​towards gender inequality in Yuni's novel by Ade Ubaidil and Dian Purnomo's novel Perempuan yang Menangis kepada Bulan Hitam. The research method used to compare these two literary works is a comparative method of qualitative descriptive analysis of comparative literary studies. The approach taken is a feminist approach. The results of this study indicate that there are differences between the culture of gender inequality in the two novels: (1) Yuni's novel presents gender injustice against Javanese women in the form of disastrous when rejecting male proposals more than three times and (2) The novel Woman Crying to the Moon Black presented gender injustice to Sumbanese women in the form of a catastrophe when they rejected the Yappa Mawine (Marriage Capture) tradition. The study uses a comparison table of elements of feminism and problamatic gender found in the novel Yuni and the Women Crying for the Black Moon. This research is expected to increase readers' interest in literary works as well as increase researchers' interest in comparative literary research